Type 1 Insulin-Like Growth Factor Receptor Nuclear Localization in High-Grade Glioma Cells Enhances Motility, Metabolism, and In Vivo Tumorigenesis - Martin, Ayelen; Fernandez, María Celia; Cattaneo, Elizabeth R.; Schuster, Claudio D.; Venara, Marcela; Clément, Florencia; Berenstein, Ariel; Lombardi, Mercedes García; Bergadá, Ignacio; Gutierrez, Mariana; Martí, Marcelo A.; Gonzalez-Baro, María R.; et al. (Frontiers in Endocrinology, 2022)
Gliomas are the most frequent solid tumors in children. Among these, high-grade gliomas are less common in children than in adults, though they are similar in their aggressive clinical behavior. In adults, glioblastoma is the most lethal tumor of the central nervous system. Insulin-like growth factor 1 receptor (IGF1R) plays an important role in cancer biology, and its nuclear localization has been described as an adverse prognostic factor in different tumors. Previously, we have demonstrated that, in pediatric gliomas, IGF1R nuclear localization is significantly associated with high-grade tumors, worst clinical outcome, and increased risk of death. Herein we explore the role of IGF1R intracellular localization by comparing two glioblastoma cell lines that differ only in their IGF1R capacity to translocate to the nucleus. In vitro, IGF1R nuclear localization enhances glioblastoma cell motility and metabolism without affecting their proliferation. In vivo, IGF1R has the capacity to translocate to the nucleus and allows not only a higher proliferation rate and the earlier development of tumors but also renders the cells sensitive to OSI906 therapy. With this work, we provide evidence supporting the implications of the presence of IGF1R in the nucleus of glioma cells and a potential therapeutic opportunity for patients harboring gliomas with IGF1R nuclear localization.